Implementing electronic health record-based anxiety and depression screening in an epilepsy clinic: Theory-based implementation strategy and pre-post quantitative outcomes using Reach, Effectiveness, Adoption, Implementation, and Maintenance - Heidi M. Munger Clary; Halley B. Alexander; Sabina Gesell; Mingyu Wan; Kelly R. Conner; Cormac O’Donovan; Jane Boggs; Christian Robles; Maria Sam; Jerryl Christopher; Christina Marini; Beverly M. Snively (Journal of Clinical and Translational Science)
Abstract